STILISTIKA GENETIK STUDI KASUS PENGGUNAAN GAYA BAHASA DALAM CERPEN "GODLOB" KARYA DANARTO - Hartono Hartono (Jurnal Penelitian Humaniora, 2003)
Abstract This research is aim to describe the style of language and its function utilized in “Gondlob”, a short story by Danarto which is include in short stories anthology of “Gondlob”. This research used the textual approach. The theorethical orientation on stylistic that is approach, which based on the assumption that the language have duty and role in the existention of textual literary. The data collected by reading and note technique. The anaysis of data used qualitative-descriptive technique. The result of research showed  that Danarto use style of words, style of sentences, and style of discourse in “Gondlob” short story by figurative speech (connotative langauge) and imagery. The figurative speech is includes: methaphor, simile, personification, irony, synecdoche, and metonymy. The kind of imagery was used  in “Gondlob” short story is rhetoric devices, which include like: repetition, rhetoric question, hyperbole, asyndeton, polysindenton, and climax. The dominant rhetoric devices was used in this short story is repetition and rhetoric question. Keywords: generic stylistic, language style, short story “Gondlob”TO